SRM grade pre-1: Communication, Language and Literacy-Term-2 Nursery - The City School (Lahore, Pakistan : The City School, 2024)
The City School's Kindergarten Resource Pack for Communication, Language, and Literacy aims to develop early language skills through interactive activities. It focuses on enhancing listening, speaking, reading, and basic writing abilities. The pack includes structured lessons, role-play, and storytelling to foster communication. It encourages creativity and builds a foundation for literacy.
Keywords: TCS - Resource Pack; TCS - KG